Topiramate: Safety and Efficacy of its Use in the Prevention and Treatment of Migraine - Minton, Ginger C. (Libertas Academica, 2011)
Migraine headaches are typically episodic in nature and may affect nearly 10% of the population. In addition to treatment, prevention of subsequent episodes or progression to a chronic migraine state is an important therapeutic area. Topiramate is a centrally acting medication approved for both the prevention of seizures and migraine headache. At this time, the exact mechanism of how topiramate assists in migraine prevention is unknown. Several large randomized, controlled trials have aided in establishing topiramate’s role in migraine prevention. Despite a favorable pharmacokinetic and adverse effect profile established in clinical trials, several additional studies, case reports and toxicology reports have demonstrated topiramate as a cause of cognitive and behavioural changes. The use of topiramate in migraine prevention can improve a patient’s quality of life and is a cost-effective option for migraine prevention.